Teaching the National Institutes of Health Stroke Scale to Paramedics (E-Learning vs Video): Randomized Controlled Trial - Koka, Avinash; Suppan, Laurent; Cottet, Philippe; Carrera, Emmanuel; Stuby, Loric; Suppan, Mélanie (JMIR Publications, 2020)
BackgroundPrompt and accurate identification of stroke victims is essential to reduce time from symptom onset to adequate treatment and to improve neurological outcomes. Most neurologists evaluate the extent of neurological deficit according to the National Institutes of Health Stroke Scale (NIHSS), but the use of this scale by paramedics, the first healthcare providers to usually take care of stroke victims, has proven unreliable. This might be, at least in part, due to the teaching method. The video used to teach NIHSS lacks interactivity, while more engaging electronic learning (e-learning) methods might improve knowledge acquisition. ObjectiveThis study was designed to evaluate whether a highly interactive e-learning module could enhance NIHSS knowledge acquisition in paramedics. MethodsA randomized controlled trial comparing a specially designed e-learning module with the original NIHSS video was performed with paramedics working in Geneva, Switzerland. A registration number was not required as our study does not come into the scope of the Swiss federal law on human research. The protocol was nevertheless submitted to the local ethics committee (Project ID 2017-00847), which issued a "Declaration of no objection." Paramedics were excluded if they had prior knowledge of or previous training in the NIHSS, or if they had worked in a neurology or neurosurgery ward. The primary outcome was overall performance in the study quiz, which contained 50 questions. Secondary outcomes were performance by NIHSS item, time to course and quiz completion, user satisfaction regarding the learning method, user perception of the course duration, and probability the user would recommend the course to a colleague. ResultsThe study was completed by 39 paramedics. There was a better overall median score (36/50 vs 33/50, P=.04) and a higher degree of satisfaction regarding the learning method in the e-learning group (90% vs 37%, P=.002). Users who had followed the e-learning module were more likely to recommend the course to a colleague (95% vs 63%, P=.02). Paramedics in the e-learning group took more time to complete the course (93 vs 59 minutes, P<.001), but considered the duration to be more adequate (75% vs 32%, P=.01). Time to quiz completion was similar between groups (25 vs 38 minutes, P=.12). ConclusionsUse of an e-learning module shows promising results in teaching the NIHSS to paramedics.